Evaluasi Usability Aplikasi Edlink pada Universitas Islam Indragiri Menggunakan Metode System Usability Scale (SUS) - Gita Novi Yanti; Dwi Yuli Prasetyo (Indra Institute Research & Publication, 2026)
Edlink is an e-learning application that has been adopted by Universitas Islam Indragiri (UNISI) as the main digital learning platform. However, no empirical evaluation has been conducted regarding its usability from the students' perspective. This study aims to measure the usability level of the Edlink application using the System Usability Scale (SUS) method. A quantitative descriptive approach was applied, involving 50 active students from the Information Systems study program as respondents selected through purposive sampling. Data were collected using the standard SUS questionnaire consisting of 10 statements on a Likert scale 1–5. The results showed that the mean SUS score was 65.60 (Standard Deviation = 11.71), classified as Grade D – Poor category. The distribution showed that 50% of respondents rated Edlink in the Poor category, 24% Good, 12% Excellent, and 14% Awful. The results of the study show that the Edlink application at UNISI still requires significant improvements, particularly in the aspects of efficiency, consistency, and user confidence. Recommendations for improvement are provided for both UNISI management and the Edlink development team.